1994
DOI: 10.1523/jneurosci.14-01-00283.1994
|View full text |Cite
|
Sign up to set email alerts
|

Target and neurotransmitter specificity of fetal central nervous system transplants: importance for functional reinnervation

Abstract: The ability of grafted fetal ventral mesencephalic dopaminergic (DAergic) neuroblasts to reinnervate the unilaterally DA denervated rat striatum and improve motoric asymmetry has been well documented in several laboratories. The importance of host target specificity, and catecholamine (CA) neurotransmitter species, in the ability of grafts to ameliorate rotational responses to apomorphine and to affect electrophysiological characteristics of striatal neurons has not been systematically studied. We unilaterally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…These differences are observed not only when comparing the axonal outgrowth from different types of grafted neurons (differing with respect to their transmitter phenotype) but also between subtypes of neurons using the same neurotransmitter, such as different subtypes of cholinergic neurons transplanted to the hippocampus (Nilsson et al, 1988;Clarke et al, 1990) or different subtypes of serotonergic neurons transplanted to striatum or spinal cord (Foster et al, 1985;Foster et al, 1988). This holds true for different types of dopaminergic neurons, as shown by the present data comparing fiber outgrowth from different subtypes of mesencephalic DA neurons and those of Zuddas et al (1991) and Hudson et al (1994) comparing the extent of fiber outgrowth from diencephalic and mesencephalic DA neurons. The mechanisms underlying this neuron-specific growth regulation in the postnatal or adult CNS are poorly known.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…These differences are observed not only when comparing the axonal outgrowth from different types of grafted neurons (differing with respect to their transmitter phenotype) but also between subtypes of neurons using the same neurotransmitter, such as different subtypes of cholinergic neurons transplanted to the hippocampus (Nilsson et al, 1988;Clarke et al, 1990) or different subtypes of serotonergic neurons transplanted to striatum or spinal cord (Foster et al, 1985;Foster et al, 1988). This holds true for different types of dopaminergic neurons, as shown by the present data comparing fiber outgrowth from different subtypes of mesencephalic DA neurons and those of Zuddas et al (1991) and Hudson et al (1994) comparing the extent of fiber outgrowth from diencephalic and mesencephalic DA neurons. The mechanisms underlying this neuron-specific growth regulation in the postnatal or adult CNS are poorly known.…”
Section: Discussionsupporting
confidence: 66%
“…This property is not shared by all DA neuroblasts: only cells derived from the ventral mesencephalon (VM) that innervate the striatum are able to establish an extensive terminal network in the host striatum. DA neuroblasts taken from other developing brain regions do not share this property (Abrous et al, 1988;Zuddas et al, 1991;Hudson et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The immunostaining and global gene-expression analysis shown here demonstrates that Dmrt5 guards the medial domain identity by restricting ventral progenitors to an accurate medial mDA fate. Given that acquisition of midbrain regional identity is critical for successful functional integration in cell therapy (29), our finding that Dmrt5 enforces a midbrain fate would have important implications in directed stem cell differentiation.…”
Section: Discussionmentioning
confidence: 95%
“…The behavioral effects of transplantation in rats are specific to mesencephalic dopamine cells. Rats transplanted with serotonergic neurons from mesencephalic raphe or dopamine neurons from hypothalamus have no improvement in behavior [17,18]. These experiments showed that innervation of the target is a specific interaction between the appropriate dopamine neuron and factors released from the denervated striatum.…”
Section: Animal Models Guiding Human Neurotransplantationmentioning
confidence: 94%